Morphological changes in kidney glomeruli of rats with chronic toxic hepatitis and its correction with lisinopril, L-arginine-L-glutamate and their combination - N. A. Rykalo; Yu. M. Berehovenko; O. V. Androshchuk (Kazimierz Wielki University, 2019)
The article presents structural changes of glomerular component of kidneys in rats with chronic toxic hepatitis (CTH) and the results of its correction with lisinopril and L-arginine L-glutamate. The influence of ACE inhibitors or angiotensin-blockers (AT) II on RAS chains is known to result in positive therapeutic effect. Addition of lisinopril to complex therapy has positively affected not only the clinical manifestations of the disease but also the functional status of kidneys, primarily due to the influence on filtration processes. Considering the significance of RAS activation in the development of hepatorenal syndrome, the aim of the work was to study the influence of ACE inhibitors (lisinopril) on kidney morphological structure during modeling of CTH, to compare its effect with hepatoprotector L-Glutargin-L-glutamate as well as to evaluate structural changes in kidney glomeruli after combined use of those drugs. The experimental study was conducted on 60 white laboratory immature rats, with initial body weight of 50-70g. CTH was modeled by intragastric administration of CCl4 oil solution in a dose of 0.1 ml / 100 g of the body weight twice a week for eight weeks. Drug correction was performed by introduction of lisinopril (in a dose of 20 mg / kg) and L-arginine-L-glutamate (in a dose of 30 mg / kg). The study revealed pronounced morphological changes in kidney glomeruli (destruction of glomerular vessels and cells) in CTH. The use of corrective factors in the experiment made it possible to decrease the severity of pathological changes. The use of lisinopril resulted in restoration of glomerular structure. After administration of L-arginine-L-glutamate, decrease of degenerative changes in kidney glomeruli was detected. Combined use of both chemical compounds mutually potentiated their action and was accompanied by membrane-stabilizing effect and intensification of aforementioned restoration processes in structural components of nephron glomeruli. Thus, it was established that after 90 days of experimentally modeled CTH, pronounced morphological changes in kidney glomeruli (destruction of vessels and glomerular cells) occurred.